2005
DOI: 10.1007/s10517-005-0320-4
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Tick-Borne Encephalitis Virus Antigenemia: Possible Pathogenesis Pathways

Abstract: Study of the proliferative potential and immunophenotype of lymphocytes and cytokine-producing capacity of mononuclear cells in patients with chronic tick-borne encephalitis virus antigenemia showed changes in T cell lymphoproliferative response, relative content of T cells and T helper inductors, immunoregulatory index, and imbalance in the production of immunoregulatory Th1 and Th2 cytokines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…Henningson et al proved that Th1 response dominates in early phase of NB [18]. Th1 pathway predominates in early TBE but then Th2 type immune prevails [19]. These observations agree with the results of our study (increased ICAM-1 concentration in CSF in the early phase of TBE and NB).…”
Section: Discussionsupporting
confidence: 93%
“…Henningson et al proved that Th1 response dominates in early phase of NB [18]. Th1 pathway predominates in early TBE but then Th2 type immune prevails [19]. These observations agree with the results of our study (increased ICAM-1 concentration in CSF in the early phase of TBE and NB).…”
Section: Discussionsupporting
confidence: 93%
“…Important host factors, as for WNV, have been demonstrated to include genetic alterations in the CCR5, OAS, and TLR3 genes, which play crucial roles in antiviral immune responses . Compromised T‐cell responses have been suggested to significantly contribute to the development of chronic TBEV infections, and, furthermore, in some of these chronic cases autoantibodies against axonal neurofilaments were found which were absent in acute cases of TBEV . A number of mutations in the viral genome have been demonstrated to mediate viral neuroinvasiveness and/or neurovirulence.…”
Section: Tick‐borne Encephalitis Virusmentioning
confidence: 99%
“…Experimental studies have demonstrated the ability of TBEV Siberian subtype to persist and produce the chronic disease in animal models (Gritsun et al 2003a ;Frolova et al 1987 ). The chronic form of TBE has been associated with mutations in the TBEV NS1 gene (Gritsun et al 2003b ) and immunological changes with defective T-cell response and imbalance in production of cytokines (Naslednikova et al 2005 ).…”
Section: Clinical Backgroundmentioning
confidence: 99%